Design and Meshing Analysis of Involute Harmonic Drive - Wang Yanyi; Tan Qing (Jixie chuandong)
The tooth profile of harmonic gear has a significant influence on the harmonic drive device performance,for the purpose to improve the harmonic drive performance,the involute tooth profile of harmonic drive is adopted as the research object,the conjugate tooth profile of harmonic drive is designed based on the envelope theory,and the conjugate exist domain,conjugate tooth profile are analyzed,the simulation analysis of the assembly station and the move locus of the conjugate tooth profile are carried out. The analysis results show that there are two conjugate exist domain and two conjugate tooth profile,however,only the first conjugate domain and the first conjugate tooth profile is effectively,the tooth profile that is designed have many advantages such as nice conjugate situation,much number of tooth profile join in conjugate,highly transmission ratio,it can provide certain reference for design and research of the harmonic drive.